Download presentation

Presentation is loading. Please wait.

Published byJayson Griffith Modified over 7 years ago

1
Warm Up 12/5 1) Is (-2, 3) a solution? 3x + y = -3 3x + y = -3 2x – 4y = 6 2x – 4y = 6 2) Find the solution by graphing y = -4 + x x + y = 6 3) Solve: y = x – 3 x + 2y = 3 No (5, 1) (3, 0)

2
Lesson 7.4A Solving Linear Systems Using Elimination

3
Keys to Know Solving with Elimination: When you combine the equations to get rid of (eliminate) one of the variables. Possible solutions are: One Solution No Solutions Infinite Solutions

4
Steps for Using Elimination 1) Write both equations in standard form (Ax + By = C) so that variables and = line up 2) Multiply one or both equations by a number to make opposite coefficients on one variable. 3) Add equations together (one variable should cancel out) 4) Solve for remaining variable. 5) Substitute the solution back in to find other variable. 6) Write the solution as an ordered pair 7) Check your answer

5
Example 1: 5x + y = 12 5x + y = 12 3x – y = 4 3x – y = 4 8x = 16 8x = 16 8 8 8 8 x = 2 x = 2 5(2) + y = 12 10 + y = 12 y = 2 The solution is: (2, 2) Step 1: Put both equations in standard form. Step 2: Check for opposite coefficients. Step 3: Add equations together Step 4: Solve for x Step 5: Substitute 2 in for x to solve for y (in either equation) Already Done y and –y are already opposites

6
Your Turn Ex. 2 2x + y = 0 Ex. 2 2x + y = 0 -2x + 3y = 8 -2x + 3y = 8 Answer: (-1, 2)

7
Example 3 3x + 5y = 10 3x + 5y = 10 3x + y = 2 3x + y = 2 3x + 5y = 10 3x + 5y = 10 -1(3x + y) = -1(2) 4y = 8 4y = 8 y = 2 y = 2 Now plug (2) in for y. 3x + 2 = 2 X = 0 Solution is : (0,2) When you add these neither variable drops out SO…. We need to change 1 or both equations by multiplying the equation by a number that will create opposite coefficients. When we need to create opposite coefficients 3x + 5y = 10 -3x – y = -2 -3x – y = -2 Multiply the bottom equation by negative one to eliminate the x

8
4) -2x + 3y = 6 x – 4y = -8 x – 4y = -8 -2x + 3y= 6 -2x + 3y = 6 2( x – 4y) = -8(2) 2x - 8y = -16 -5 y = -10 -5 y = -10 y = 2 y = 2 Now plug (2) in for y into any of the 4 equations. -2x + 3(2) = 6 -2x + 6 = 6 -2x = 0 x = 0 x = 0 Solution is: (0, 2)Check your work! We will need to change both equations. We will have the y value drop out.

9
Your Turn Ex. 55x – 2y = 12 2x – 2y = -6 Ex. 6-3x + 6y = 9 x - 2y = -3 x - 2y = -3 Ex. 72x + 4y = 8 x + 2y = 3 x + 2y = 3 (6, 9) 0=0 Infinite solutions 0=2 No Solutions

10
What would happen when lines are coinciding? (The Same LINE or equation) Make up one for us to work out on the board. What happens when lines do not intersect? (parallel or same slope) Make up one for us to work out on the board. Conclusions: If the variables disappear and you have a true statement: Infinite solutions If the variables disappear and you have a false statement: No solutions

11
Summary: Of the three methods you have learned for solving systems of equations, which do you like the best and why, and which do you like the least and why? Of the three methods you have learned for solving systems of equations, which do you like the best and why, and which do you like the least and why? HW: WS 7.4 HW: WS 7.4

Similar presentations

© 2023 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google